Hydration and Thermal Expansion in Anatase Nanoparticles. Issue 32 (6th June 2016) - Zhu, He; Li, Qiang; Ren, Yang; Fan, Longlong; Chen, Jun; Deng, Jinxia; Xing, Xianran
Abstract : A tunable thermal expansion is reported in nanosized anatase by taking advantage of surface hydration. The coefficient of thermal expansion of 4 nm TiO2 along a ‐axis is negative with a hydrated surface and is positive without a hydrated surface. High‐energy synchrotron X‐ray pair distribution function analysis combined with ab initio calculations on the specific hydrated surface are carried out to reveal the local structure distortion that is responsible for the unusual negative thermal expansion.